2011
DOI: 10.1007/s10961-011-9210-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and the US national innovation system: continuity and change

Abstract: A substantial literature on nanotechnology innovation and commercial development has characterized several elements of these phenomena as constituting new developments in the US national innovation system. Among these elements are the (asserted) ''post-academic'' nature of US universities' involvement with nanotechnology R&D, and federal funding of nanotechnology R&D on goals related to economic competitiveness. This paper challenges the ''novelty'' of these elements, while suggesting that other elements of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…First, there are many commercial innovations that are not patented. Second, many patents have never been developed into commercially valuable forms [27,47]. However, there have been plenty of studies that demonstrated high correlations between patents and various indicators of innovation, such as the Small Business Administration Innovation Database and corporate R&D activities [48][49][50].…”
Section: Methods and Analysismentioning
confidence: 99%
“…First, there are many commercial innovations that are not patented. Second, many patents have never been developed into commercially valuable forms [27,47]. However, there have been plenty of studies that demonstrated high correlations between patents and various indicators of innovation, such as the Small Business Administration Innovation Database and corporate R&D activities [48][49][50].…”
Section: Methods and Analysismentioning
confidence: 99%
“…Youtie et al (2008) reviewed the rapid growth of nanotechnology publications in different countries between 1990 and 2006 and showed that the US has been one of the leading countries in nanotechnology research and that it has ranked first in terms of the quality of publications. Furthermore, the major US federal support of nanotechnology academic research is provided by the interagency program of the NNI which is mostly motivated by an interest in economic outcomes (Mowery 2011). The public funding of nanotechnology academic research fosters the emergence of collaboration among universities, industry and government and highlights a Triple-Helix of relationships between these organizations (Etzkowitz 2008;Leydesdorff and Meyer 2006;Schultz 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The linear model posits that research, development, manufacturing, and market phases are moved through in a sequential manner. As Mowery (2011) indicates, we are in a "pro-patent era" in which high rates of patenting are encouraged in universities and other research-intensive institutions as well as in companies. A variation to both the linear and double-boom models is the concept that science-based innovation proceeds through contemporaneous advancements in research and commercialization.…”
Section: Literature Reviewmentioning
confidence: 99%